Proceedings Frontiers in Education 35th Annual Conference
DOI: 10.1109/fie.2005.1612204
|View full text |Cite
|
Sign up to set email alerts
|

Memview: A Pedagogically-Motivated Visual Debugger

Abstract: -Novice programmers often have difficulty understanding the interactions between the objects in their programs. Many studies have shown that visual representations of computer memory can aid students' comprehension. One such representation, developed by Gries and Gries, divides computer memory into three areas: one for the call stack, one for static objects allocated on the heap ("static space"), and one for normal heap objects ("object space"). Memview, an extension to the DrJava IDE developed at Rice Univers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
(6 reference statements)
0
4
0
Order By: Relevance
“…The Sorva et al review also references a review on algorithm visualisation by Hundhausen et al [288] that was not identified in our search because it was published in 2002; however, we mention it here for the interested reader. As the 2013 review by Sorva et al is recent and comprehensive (64 pages and well over 200 references), in this section we do not discuss papers that were covered in that review and also identified in our search [66,97,228,312,330,353,362,453,535,635]. The remaining papers can be classified as either program visualisation, predominantly in Java, or algorithm visualisation.…”
Section: Toolsmentioning
confidence: 99%
“…The Sorva et al review also references a review on algorithm visualisation by Hundhausen et al [288] that was not identified in our search because it was published in 2002; however, we mention it here for the interested reader. As the 2013 review by Sorva et al is recent and comprehensive (64 pages and well over 200 references), in this section we do not discuss papers that were covered in that review and also identified in our search [66,97,228,312,330,353,362,453,535,635]. The remaining papers can be classified as either program visualisation, predominantly in Java, or algorithm visualisation.…”
Section: Toolsmentioning
confidence: 99%
“…Lastly, the front-end itself is the controller, while we aim at giving full control to the teacher through its control script, this is summarized in Table I. Examples of enhanced visualization not provided by visual debuggers include stepping on expressions (34,36), showing stack and heap (37,38), or adding role-based animation (39). As illustrated in Table III, our observation is that many specific teaching requirements are not covered by existing tools, which is precisely what motivated us to develop EasyTracker.…”
Section: Related Workmentioning
confidence: 99%
“…Compared to existing line-by-line program visualization tools such as Python Tutor, CrossCode may have a greater potential to scale to more complex code as it aggregates operations rather than presenting them at a static level of detail. However, challenges remain in extending the current design to common programming paradigms such as object-oriented programming, which will require specialized abstractions (i.e., abstraction based on syntax tree will not solely capture models of classes and concepts such as inheritance) and representations (e.g., [15]). Other considerations, such as scaling across multiple files or to more complex states, will require specialized mechanisms for managing complexity in the Control Flow View and the Data View.…”
Section: Study Implicationsmentioning
confidence: 99%